Tata Kelola Kolaboratif Pada Program Nasional Pemberdayaan Masyarakat Dalam Penanggulangan Kemiskinan (Universitas Medan Area, 2021)
This article aims to describe the role of the stakeholders involved in forming collaborative governance in community empowerment programs. The problem is focused on poverty alleviation. To approach this problem, the theoretical references from Ansell and Gash 2007 regarding the implementation of collaborative governance are used. Data is collected through literature study based on previous research and direct observation and analyzed qualitatively. This study concludes that research where collaborative governance among stakeholders, where the government is a facilitator, community activeness as well as institutional strengthening within it, as well as private sector assistance in community empowerment will produce a real contribution in national poverty reduction. The poor are no longer the object of mitigation, but rather the subject which in the whole process involves the community. With the empowerment program, the community has a job and eliminates the poor culture of the poor who only depend on direct assistance from the government.